Communicating and mobile systems the [symbol for pi]- calculus - Milner, Robin (Cambridge University, 1999)
In this book Robin Milner introduces a new way of modelling communication. He treats computers and their programs as themselves built from communicating parts, rather than adding communication as an extra level of activity. But the aim of the book is to develop a theory, the [pi]-calculus, in which these things can be treated rigorously. The [pi]-calculus differs from other models of communicating behaviour mainly